Negotiating the holistic turn : the domestication of alternative medicine - Fadlon, Judith, 1955- (State University of New York Press, 2005)
"Combining ethnographic study with quantitative data, Judith Fadlon explains the popularity of alternative medicine, as well as the ease with which individuals now move between conventional and alternative medicine and between different alternative modalities. She concludes that alternative medicine has been undergoing domestication, a process by which the foreign is rendered familiar. Although the focus of the study is urban Israel, it is argued that domestication is a major force at work in a number of Western countries."--BOOK JACKET.